2010
DOI: 10.1088/0268-1242/25/3/034004
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic condensation in a double-layer graphene system

Abstract: The possibility of excitonic condensation in a recently proposed electrically biased double-layer graphene system is studied theoretically. The main emphasis is put on obtaining a reliable analytical estimate for the transition temperature into the excitonic state. As in a double-layer graphene system the total number of fermionic "flavors" is equal to N = 8 due to two projections of spin, two valleys, and two layers, the large-N approximation appears to be especially suitable for theoretical investigation of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 56 publications
3
47
0
Order By: Relevance
“…Under such conditions, according to Ref. [36], the exciton gap becomes exponentially small around 1 mK. In this case, a small amount of disorder makes exciton condensation impossible [37].…”
Section: Exciton Order Parametermentioning
confidence: 95%
See 1 more Smart Citation
“…Under such conditions, according to Ref. [36], the exciton gap becomes exponentially small around 1 mK. In this case, a small amount of disorder makes exciton condensation impossible [37].…”
Section: Exciton Order Parametermentioning
confidence: 95%
“…References [25][26][27][28][29]36] considered a system with two graphene layers separated by an insulating layer. The dielectric barrier between the layers completely suppresses the interlayer tunneling and destroys the AFM order.…”
Section: Exciton Order Parametermentioning
confidence: 99%
“…These features suggest a unique venue for searching for 1 new interaction phenomena. Accordingly, double-layer graphene has attracted significant theoretical interest and has already become a subject of intense debates about predictions for both Coulomb drag [22][23][24][25][26][27][28] and excitonic superfluidity 15,29 . As for experiment, a recent publication 16 reported Coulomb drag in double-layer graphene in zero magnetic field B by using devices in which the layers were separated by a several-nanometre-thick alumina barrier and had charge carrier mobilities µ ∼ 10,000 cm 2 V −1 s −1 .…”
mentioning
confidence: 99%
“…Quite recently a suggestion has been made to use graphene layers as components of bilayer systems [14][15][16][17][18]. Further investigations revealed that a serious problem in this case is screening of Coulomb interaction between the electron and the hole [19,20]. The screening effect is most dangerous in the regime of weak coupling, when the size of electron-hole pairs significantly exceeds the average interparticle distance (BCS regime).…”
Section: Introductionmentioning
confidence: 99%